Feeding Bacillus subtilis ATCC19659 to Broiler Chickens Enhances Growth Performance and Immune Function by Modulating Intestinal Morphology and Cecum Microbiota - Mohamed, Taha M.; Sun, Weizhong; Bumbie, Gifty Z.; Elokil, Abdelmotaleb A.; Mohammed, Khaled Abuelezz Fouad; Zebin, Rao; Hu, Ping; Wu, Liuting; Tang, Zhiru (Frontiers in Microbiology, 2022)
This study investigated dietary supplementation with Bacillus subtilis (BS) ATCC19659 on growth performance, biochemical indices, intestinal morphology, and cecum microflora in broiler chicks. A total of 600 Arbor 1-d Acres broilers of either sex were allotted to 5 treatments: Chicks were fed a corn- and soybean-based diet (CON); Chicks were fed basal diet contained 500 mg ZnB/kg (ZnB); Chicks were fed basal diet contained 1×108 CFU/g feed of BS-ATCC19659(BS-1); Chicks were fed basal diet contained 3×108 CFU /g feed of BS-ATCC19659 (BS-3); Chicks were fed basal diet contained 5×108 CFU/g feed of BS-ATCC19659 (BS-5). Each treatment comprised of 6 replicates with 20 birds for each replicate pen. Chicks in BS-5 and BS-3 groups had higher body weight at 21st and 42nd days and average daily gain from 1 to 21 d than that in the CON group (P <0.05). Chicks in BS-5 and ZnB groups had higher serum antioxidant activities and immunity response than that in the CON group (P <0.05). Compared with the CON group, the liver mRNA abundance of GHR, TGF-β, IGF-1, IFN-γ, SOD, CAT, and GPX of chicks in three BS groups and the ileum villus length (µm) of chicks in BS-3 and ZnB groups were increased (P <0.05). Compared with the CON group, the villi height to crypt depth ratio of the ileum of chicks in BS-5 and BS-3 groups, and the crypt depth and villi height to crypt depth ratio of the jejunum in BS-5 and ZnB groups (P <0.05) were increased (P <0.05). The abundance of the Cyanobacteria phyla in the cecum decreased in response to treatment with both BS-ATCC19659 and ZnB groups (P <0.05). Compared with the CON group, the cecum abundance of genera GCA-900066575 (Lachnospiraceae), Anaerofustis, Papillibacter (Firmicutes phylum) in three BS groups were increased (P< 0.05); The abundance of genus Escherichia-Shigella reduced in the BS-3 group (P <0.05). Compared with the CON group, the cecum abundance of genus Clostridia_unclassified in ZnB and BS-5 groups were decreased (P < 0.05) of broilers. Generally, Bacillus subtilis ATCC19659 as feed additive positively affected growth performance, immunity response and cecal microflora of broilers.